Penyuluhan Kesehatan Bahaya ISPA dan Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) - Zuraida Sagala; Laras Puspita Dewi; Haninda Noer Safitri; Rina Pebriani; Alifvia Nurcahyani; Fadhillah A Virsyada; Aida Yulistia Manu Hunga; Annisa Maulidya Rachma; Yuni Christina Angelika (Universitas 45 Surabaya, 2024)
ARI is still a major health problem in Indonesia. The purpose of health counseling in RW 01 Kalibaru, Cilincing North Jakarta is to increase public awareness about the dangers of ARI and the importance of Clean and Healthy Living Behavior (PHBS). The methods used include interactive lectures, questions and answers, and demonstrations of making hand sanitizers. The activity was attended by 36 participants, the majority of whom were female (97.1%) with an age range of 21-65 years. To measure participants' understanding, an evaluation was conducted after the material was given. The results showed that 97.1% of participants had good knowledge about ARI and PHBS after the counseling was given. Participants were able to correctly answer questions related to the definition of ARI, symptoms, prevention, and principles of PHBS. In conclusion, this counseling is effective in increasing community knowledge about ARI and PHBS. It is expected that this better knowledge can encourage behavioral changes in the community.